Interseksionalitas Dalam Film Asmaa: Analisis Gender, Stigma, dan Kelas Masyarakat Patriarkal Mesir - Yunita, Novi; Rohanda, Rohanda; Nurhasan, Muhamad (Aksara: Jurnal Bahasa dan Sastra, 2025)
This study aims to examine the form of intersectionality experienced by female characters in the film 'Asmaa' by Amr M Salama. Therefore, the theory used to analyze data based on the problems found is the theory of intersectionality from the perspective of Kimberle Crenshaw. The method used in this research is descriptive qualitative method. The type of data used by researchers in this study is qualitative data in the form of screenshots of scenes from the film Asmaa and then analyzed verbally. Based on this analysis, the results of this study show that Asmaa, as the main character in the film, experiences three forms of intersectionality oppression, namely gender, health stigma, and social class in Egyptian patriarchal society.Keywords: intersectionality, patriarchy, HIV, film